Examination of five- and four-subtest short form IQ estimations for the Wechsler Intelligence Scale for Children-Fifth edition (WISC-V) in a mixed clinical sample. Issue 1 (2nd January 2022) - Lace, John W.; Merz, Zachary C.; Kennedy, Erin E.; Seitz, Dylan J.; Austin, Tara A.; Ferguson, Bradley J.; Mohrland, Michael D.
Abstract: Evaluating general cognitive ability (i.e., intelligence) is common in neuropsychological practice, and identifying abbreviated assessments of intelligence is often advantageous. Despite the Wechsler Intelligence Scale for Children, Fifth Edition's (WISC-V) widespread contemporary use, limited research has identified clinically useful short form (SF) full scale IQ (FSIQ) estimations in clinical samples. This study sought to address this gap in the literature. Two hundred sixty-eight pediatric participants ( M age = 9.79; 69% male; 88% Caucasian/White) who underwent psychological/neuropsychological evaluation were included. Mean scores for WISC-V scores fell in the low average-to-average ranges, consistent with the clinical nature of this sample (e.g., M FSIQ = 85.3). Ten unique SF combinations with five (pentad) and four (tetrad) subtests, each intentionally selected to represent a breadth of domains subsumed by WISC-V FSIQ, were described by summing subtest age-corrected scaled scores. Regression-based and prorated FSIQ estimates were calculated, and mean differences suggested some prorated estimates should be arithmetically adjusted. Both regression-based and prorated/adjusted methods provided FSIQ estimates that were accurate within five Standard Score points of true FSIQ for approximately 81–92% (pentad) and 65–76% (tetrads) of participants. Prorated/adjusted estimates appeared to provide somewhat better accuracy than regression-based estimates. Relationships between SFs and true FSIQ did not appear to be moderated by participant age, gender, nor how many WISC-V subtests were administered to participants within this archival sample (i.e., 7 vs. 10). Implications of these findings, including benefits, detriments, and other considerations of each SF combination, in addition to limitations of this study, are discussed in detail.